2019
DOI: 10.1002/pen.25181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing on the permeation properties of a thermoplastic elastomer

Abstract: The use of plastic films with specific diffusion or permeation properties for industrial applications has grown at a considerable rate. Some useful applications are found in medical devices, bioreactors, and combustible fuel storage where polymer films function as separation membranes that allow permeation of different gases at different rates. In this work, the permeation and diffusion properties of a polyester-based thermoplastic polyurethane (TPU) were investigated. TPU injected and extruded specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This process can change the polyurethane mechanical properties, as it can be associated with changes in the modulus of elasticity and ultimate tensile strength. [35][36][37] This reorganization was observed during PU annealing and depended on the annealing time, temperature, and presence of liquids like water between the polymer chains. None of the treatment cycles seem to have an impact on the endothermal events, suggesting that the excipient solutions do not induce any remarkable change in the organization of hard domains.…”
Section: Discussionmentioning
confidence: 99%
“…This process can change the polyurethane mechanical properties, as it can be associated with changes in the modulus of elasticity and ultimate tensile strength. [35][36][37] This reorganization was observed during PU annealing and depended on the annealing time, temperature, and presence of liquids like water between the polymer chains. None of the treatment cycles seem to have an impact on the endothermal events, suggesting that the excipient solutions do not induce any remarkable change in the organization of hard domains.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to the better mechanical properties. 26 From the experimental results, it can be seen that for 3D printed TPU products, heat treatment can allow them to effectively improve their toughness and strength while maintaining their original shape.…”
Section: Effect Of Heat Treatment On the Mechanical Properties Of 3d ...mentioning
confidence: 98%
“…The chemical shifts at 1.18−1.21 ppm could be related to CH 3 (i, j) at the side chain. Combined with FT-IR and 1 H NMR spectra, it can be concluded that the copolymers are successfully prepared as addressed in Scheme 2.…”
Section: Dsc and Thermogravimetric Analysismentioning
confidence: 98%
“…As one of the most widely used polymer materials, thermoplastic elastomers (TPEs) exhibit elasticity at ambient temperature and can be processed easily by melt processing techniques or injection molding . TPEs such as poly­(styrene-butadiene- b -styrene)­s, poly­(ether-urethane)­s, poly­(ester-ether)­s, and poly­(ether-amide)­s have been widely used as films, gas-separation membranes, shape-memory materials, self-healing materials, and sealing materials .…”
Section: Introductionmentioning
confidence: 99%